A structured literature review of simulation modelling applied to Emergency Departments: Current patterns and emerging trends. (December 2018) - Salmon, Andrew; Rachuba, Sebastian; Briscoe, Simon; Pitt, Martin
Abstract: The public importance, wait-for-treatment ethos and clear geographic layout of Emergency Departments (EDs) has contributed to them being one of the most commonly modelled systems in healthcare Operational Research (OR). EDs are presently contending with higher than ever attendances, to which clinical research does not appear to have a comprehensive solution, whilst OR methodologies still need to command the trust of decision makers. With potentially greater acceptance of OR methodologies driven by heightened efforts to engage clinicians in evidence based approaches, we present a comprehensive review of the current literature. Whilst not the first in this area, our review is more broadly focused and thus able to serve both as a resource for modellers of methodology and study design, and as an introduction for decision makers. Our systematic literature search aimed to identify all English language papers from the year 2000 onward. We categorise papers using the defined dimensions of purpose, application area, method, scope and sponsor (originator). Of 254 retrievals, we find that new publications are currently appearing at approximately 25 per year, up seven fold since 2000. We find positive trends in terms of recent publications (75% since 2008) as well as a trend towards achieving publication in journals, including healthcare related journals, which may assist in bringing simulation to a clinical audience and facilitating future engagement. The majority of projects appear to be of academic origin, based on Discrete Event Simulation, and focused on capacity, process and workforce issues at an operational level. However, the use of hybrid modelling may be associated with a more strategic outlook, as do projects originated at the request of healthcare organisations. We present a selection of case studies to illustrate both our classification and findings, and suggest directions for further research.